2021
DOI: 10.1186/s13256-021-02755-z
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic injury to long thoracic nerve following thoracotomy for right thoracic scoliosis in Marfan syndrome: a case report

Abstract: Background Patients with Marfan syndrome commonly require spinal deformity surgery. The purpose of this case report is to present a rare thoracotomy complication. We present the management of such a patient. Case summary In a known case of Marfan syndrome, an 18-year-old Persian man was admitted to our hospital with scoliosis. The patient underwent radiological examinations, and thoracic scoliosis of 70° was diagnosed. A right thoracotomy for anter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Midline sternotomy seems to also confer risk for chest wall asymmetry and the development of scoliosis through abnormal growth. Other authors have suggested that long thoracic nerve damage during a high thoracotomy may lead to the unilateral denervation atrophy of the serratus anterior facilitating development for scoliosis 5,6,12. Still, other studies point to asymmetry caused by excessive scarring as the causative agent 5,7,11…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Midline sternotomy seems to also confer risk for chest wall asymmetry and the development of scoliosis through abnormal growth. Other authors have suggested that long thoracic nerve damage during a high thoracotomy may lead to the unilateral denervation atrophy of the serratus anterior facilitating development for scoliosis 5,6,12. Still, other studies point to asymmetry caused by excessive scarring as the causative agent 5,7,11…”
mentioning
confidence: 99%
“…Other authors have suggested that long thoracic nerve damage during a high thoracotomy may lead to the unilateral denervation atrophy of the serratus anterior facilitating development for scoliosis. 5,6,12 Still, other studies point to asymmetry caused by excessive scarring as the causative agent. 5,7,11 Previous research has focused primarily on characterizing the incidence of thoracogenic scoliosis.…”
mentioning
confidence: 99%